Solar Alpha Particle Radiation Increases Human Mortality - Examples from the Neoplasms Mortality in Europe and the Mediterranean (Global Journal of Science Frontier Research, 2024)
A dangerous phenomenon for humanity is described. In the joint analysis of data from satellites in orbit around the Earth and from the health statistics source EUROSTAT, it became clear that, by some mechanism, flows of positively charged particles with high energy entering the Earth's orbit increase mortality on the planet's surface. The increase in mortality is in a band of maximum risk in the Northern Hemisphere, parallel to the Equator and bounded by the parallels of 30° and 50° north latitude. Examples are given for the European Union mortality from neoplasms, confirming the described phenomenon. A hypothetical mechanism based on observational evidence has been proposed, according to which this dangerous phenomenon is due to solar alpha particles of high energy sufficient to overcome the atmosphere's resistance and reach the Earth's surface in a limited area of maximum death impact.
Keywords: mortality; neoplasms; satellites GOES; cosmic alpha radiation; EUROSTAT